2016
DOI: 10.1039/c5ra26040j
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein isolate/gum arabic intramolecular soluble complexes improving the physical and oxidative stabilities of conjugated linoleic acid emulsions

Abstract: Protein–polysaccharide intramolecular soluble complexes are proved to have superior emulsifying properties in stabilizing PUFAs-based emulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Both procedures did not affect the degradation rate of β‐carotene in the sunflower oil– water emulsions stabilised by WPI and pectin (Xu et al ., ). The mixed layer emulsions have been prepared by WPI and gum Arabic soluble complexes, which had superior emulsifying property and protection against the oxidation of conjugated linoleic acid in comparison with individual protein or polysaccharide (Yao et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Both procedures did not affect the degradation rate of β‐carotene in the sunflower oil– water emulsions stabilised by WPI and pectin (Xu et al ., ). The mixed layer emulsions have been prepared by WPI and gum Arabic soluble complexes, which had superior emulsifying property and protection against the oxidation of conjugated linoleic acid in comparison with individual protein or polysaccharide (Yao et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In previous works, an intramolecular soluble proteinpolysaccharide complex was found to efficiently stabilize emulsions and protect PUFA (Li et al, 2012a(Li et al, , 2013Yao et al, 2016). In a previous study, we systematically compared the air-water and oil-water interfacial properties of NGBLG, BLGF, and BLGNP, and found that their foaming and emulsifying properties were in the order of BLGF > NGBLG > BLGNP (Hu et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…(Lee et al, 2007;Phoon et al, 2014) Noncovalent interaction WPI-gum Arabic, Tannic acid-cuttlefish skin gelatin, Gliadin-proanthocyanidins ⋅Electrostatic interaction ⋅Antisolvent technology Be able to prepare Pickering particles; Compact interfacial layer; More antioxidative emulsifiers; Higher oxidative stability of PUFAs in emulsions. (Aewsiri et al, 2010;Huang et al, 2017;Yao et al, 2016) Fibrillation Innovative approach. (Chang et al, 2018;Mohammadian & Madadlou, 2016;Serfert et al, 2014) PUFAs, polyunsaturated fatty acids; WPI, whey protein isolate.…”
Section: Maillard Reactionmentioning
confidence: 99%
“…Intramolecular soluble complexes of WPI and Gum Arabic (GA) at pH 4.4 were applied to stabilize conjugated linoleic acid emulsion that exhibited a significantly lower oxygen consumption than that stabilized with WPI or GA alone, decreasing from 1.85 μmol/(mL·min·μm), 0.35 μmol/(mL·min·μm) to 0.05 μmol/(mL·min·μm) (Yao et al., 2016). The insoluble complexes, such as complex coacervates also provide an oxygen barrier.…”
Section: Interfacial Structure Design For Improving Oxidative Stabilitymentioning
confidence: 99%